Scattering of Plane Electromagnetic Waves by Lattices of Spherical Dielectric Resonators with Degenerate Lower Types of Natural Oscillations - О. О. Трубін (Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni Kììvsʹkij Polìtehnìčnij Ìnstitut: Serìâ Radìotehnìka, Radìoaparatobuduvannâ, 2023)
The problem of scattering of plane electromagnetic waves on lattices of spherical dielectric resonators (DRs) with low magnetic oscillations is considered. The results of theoretical calculations of complex coefficients of mutual coupling of spherical dielectric resonators in open space for cases of excitation of degenerate types of oscillations are presented. The expressions found coincide with those obtained earlier for the special case of oscillations of resonators excited along or perpendicular to the line connecting their centers. The main regularities of the change in the coupling coefficients with variations in the coordinates of the resonators in the transverse plane are considered. Analytical expressions for c-functions are found for the field of fundamental magnetic oscillations of a resonator and a plane wave in open space. On the basis of the obtained formulas, with the help of the perturbation theory, the characteristics of the scattering of plane waves on a square lattice of spherical DRs with basic degenerate magnetic oscillation types are calculated and studied. The distribution of the scattering field in the wave zone of the grating is studied for different angles of incidence. The regions of variation of the angles of incidence are determined, in which the scattering amplitude of a lattice constructed on the basis of spherical DRs differs most noticeably from DR lattices of other shapes with nondegenerate types of oscillations. The polarization characteristics of scattered waves in the far zone of the lattice are calculated. It is noted that, in contrast to the lattices of pseudorotating cylindrical DRs with the main magnetic types of oscillations, lattices based on spherical resonators are characterized by a more complex distribution of the polarization of scattered waves. In the wave zone of the lattice, scattered waves of all three types of polarization, linear, circular, elliptical, can be observed. The obtained results significantly expand the possibilities of developers, since allow us to create electrodynamic models of lattices, as well as other devices in the millimeter and infrared ranges, built on the basis of the use of spherical resonators with oscillations of the main types. Such lattices can be used in antennas, passive reflectors, and other devices of modern optical communication systems.